2014
DOI: 10.1055/s-0033-1358457
|View full text |Cite
|
Sign up to set email alerts
|

Wie wirksam ist intensive Aphasietherapie unter regulären klinischen Bedingungen? Die deutschlandweite Aphasieversorgungsstudie FCET2EC

Abstract: Zusammenfassung Die seit dem 1.2.2012 vom BMBF gef?rderte Aphasieversorgungsstudie FCET2EC (From con?trolled experimental trial to=2 everyday communication) ist international die erste multizentrische randomisierte kontrollierte Studie (?randomized controlled trial?) zum Nachweis der Wirksamkeit intensiv durchgef?hrter Sprachtherapie bei Schlaganfallpatienten mit chronischer Aphasie (d.?h. >6 Monate nach akutem Schlaganfall anhaltend). Ziel dieser Studie ist der statistische Nachweis auf einem hohen methodisch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Furthermore, according to the authors, this network could also be effectively modulated by non-invasive brain stimulation. It is also probable that the picture naming training itself might have induced such neuroplastic changes as language therapy can significantly improve language functions in the chronic phase after stroke (Breitenstein et al, 2017). Previous studies reported increased activity in the right Resting state functional connectivity: this figure shows the spatial distribution of the network nodes and the correlation scores before and after treatment between the significant ROIs activity.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, according to the authors, this network could also be effectively modulated by non-invasive brain stimulation. It is also probable that the picture naming training itself might have induced such neuroplastic changes as language therapy can significantly improve language functions in the chronic phase after stroke (Breitenstein et al, 2017). Previous studies reported increased activity in the right Resting state functional connectivity: this figure shows the spatial distribution of the network nodes and the correlation scores before and after treatment between the significant ROIs activity.…”
Section: Discussionmentioning
confidence: 90%
“…At present, speech-language therapy (SLT) in behavioral science is still the mainstream treatment for aphasia (Fridriksson and Hillis, 2021). High-dose and high-intensity SLT is beneficial to the functional recovery of PSA (Breitenstein et al, 2017), but when SLT is more than 2 h per day, the benefit does not increase significantly (Rehabilitation and Recovery of People with Aphasia after Stroke, 2022). In the context of limited medical resources, treatment strategies need to be reconsidered based on the existing evidence to maximize language recovery and cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%